Consumer Buying Behavior and Perceived Value of Locally Produced Vegetables in San Antonio, Nueva Ecija - Banzon, Ian; Santos, Angelica; De Leon, Clarizza (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated consumer preferences, perceived value, and buying behavior toward locally produced vegetables in San Antonio, Nueva Ecija. It was guided by the view that consumer behavior is shaped by demographic characteristics, purchasing determinants, perceived product value, and market conditions, with the determinants examined through a SWOT perspective. The study used a descriptive research design and gathered data through a researcher-developed survey questionnaire and an interview guide. Respondents included 100 adult consumers who regularly purchased vegetables for household use, along with selected local vegetable producers and sellers who provided contextual insights on supply, pricing, quality, and demand. Quantitative data were analyzed using frequency, percentage, weighted mean, ranking, and descriptive analysis, while qualitative responses were interpreted thematically. Findings showed that consumers generally preferred locally produced vegetables because of freshness, quality, food safety, taste, health benefits, and support for local farmers. They also associated local vegetable purchasing with contribution to the local economy, environmental sustainability, and community welfare. However, seasonal shortages, inconsistent supply, limited availability, price fluctuations, market distance, and seller inconsistency remained challenges. The study concluded that favorable attitudes and high perceived value sustain consumer demand despite existing market constraints. It recommended that farmers and sellers maintain freshness, quality, food safety, and proper handling, while local government units and agricultural offices strengthen market support, supply chain efficiency, availability, and promotional initiatives. The study supports SDG 2, SDG 8, SDG 11, and SDG 12 through its focus on sustainable agriculture, local livelihood, community-based food systems, and responsible consumption. Its sustainability impact lies in promoting agricultural resilience, rural economic support, environmental responsibility, and stronger local food systems.